Visualisasi Perbandingan Anggaran Pendapatan Dan Belanja Daerah (APBD) Pemerintah Provinsi Kabupaten Dan Kota Di Indonesia Periode 2010-2014 - Taufik Dwi Saputra Tanwir; Johan Setiawan (Universitas Multimedia Nusantara, 2016)
Regional Income and Expenditure Budget (APBD) is a very important thing in the progress of a region. APBD is an indicator of public welfare level in a region. Data of APBD that is shared on the official website data.go.id is still hard to read and understood, and for that reason the author will compare the budget value of APBD in every province, district, and city by using visualization. The method the author used is Visual Data Mining by creating an APBD visualization dashboard according to provinces, districts, and cities. Tableau Software is used to create the dashboard because Tableau allows an interactive, easy-to-use dashboard for analyzing lots of data. Besides, Tableau is already supported by many platform such as web based, iPhone app, also Android app, and this application is one of the common for visualization so there are a lot of sources to get more information and to develop visualization. The result of this research could help the government in reevaluating the APBD financial budget in every region in Indonesia. This research can help the people to know the APBD budget applied in every region. Index Terms-Regional Income and Expenditure Budget (APBD), financial, visualization.